Preparedness of health professions students for interprofessional collaboration: a mixed method study. Issue 1 (2nd January 2023) - Itzhaki, Michal; Katz Leurer, Michal; Warshawski, Sigalit; Avrech Bar, Michal
ABSTRACT: Interprofessional collaboration (IPC) improves communication between healthcare workers and healthcare delivery. This study aimed to explore the reflections of final year health professions students on their preparedness for IPC. Participants were 183 fourth-year nursing, occupational therapy (OT), and physical therapy (PT) students. Data were collected using the Interdisciplinary Education Perception Scale, three open-ended questions, and one question assessing students' experience with the problem-based learning (PBL) method. The findings reveal that only OT students experienced the PBL method and they were more positive than others regarding competence, readiness, and willingness to cooperate with other health professions. Most students valued the preparation they had received and referred to: structure and content of the curriculum, informal aspects of the curriculum, and aspects of clinical practice. Approaches involving interprofessional groups of students working together in tutorial situations were classified as most contributing to IPC and integration into the multidisciplinary team in clinical practice.